Buffalo whey proteins performance at the oil/water interface: rheology characterization of the interfacial films - Leandro F. Bustos; Víctor M. Pizones Ruiz-Henestrosa; Cecilio Carrera Sánchez; Franco E. Vasile; Oscar E. Pérez (Revista Científica)
Whey proteins can form thin layers at the interface of non-miscible liquids like oil drops and water by emulsifying. The interfacial activity and the rheology of the interfacial films constitute a crucial aspect in assessing ingredients’ ability to form and stabilize emulsions. Although cow-origin whey protein concentrates (WPC) have been extensively used in the food industry, the WPC from buffalo (BWPC) still needs to be studied. In this context, the objective of this work was to explore the interfacial activity and the viscoelastic properties of BWPC at the oil-in-water (O/W) interfaces. WPC was used for comparison. With this purpose, BWPC and WPC were dispersed at 2.6x10-3 – 1.6% w/v in 10 mM phosphate buffer (pH 7) and equilibrat-ed at four °C for 24 h. Then, the equilibrium interfacial pressure (πeq) was registered through the Wilhelmy plate method. Additionally, adsorption dynamics at the O/W interface at protein concentrations of 0.5 and 1% were obtained over three h with a drop tensiometer. Subsequently, the rheological dilatational behavior (10% deformation amplitude and 0,1 Hz of angular frequency) was evaluated. Plate tensiometry showed that πeq of BWPC and WPC solutions increased from 9.9 to 16.7 mN/m and 11.5 to 15.0 mN/m, respectively, and conform protein concentration increased. An intersection between π – concentration isotherms was observed, indicating that below protein concentration of 1.3x10-2%, the πeq of WPC was higher than BWPC. This observation could be attributed to compositional differences and the possibility of generating different structural patterns in the interface. The drop tensiometer displayed that π increased with time for both protein concentrates, indicating the protein adsorption at the O/W interface. Interfacial rheology results indicated a gradual increase in the solid or elastic character (Ed) over time for both types of proteins, indicating more cohesive and packed structures. Ed of BWPC was higher than WPC at the lowest protein concentration, while the opposite also occurred. This behavior can be explained by considering that the higher the protein concentration, the stronger interactions among BPWC proteins occur. In conclusion, BWPC increased the interfacial pressure to a greater extent than WPC and concomitantly formed films with a higher solid character. These findings contribute to considering the use of BWPC as an efficient emulsifier agent with the benefits of adding value and minimizing the environmental impact of this byproduct.